PENERAPAN MODEL PEMBELAJARAN ANCHORED INSTRUCTION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK - Dedi Kuntadi; Hellen Lie Grace Ghautama (UIN Sunan Gunung Djati Bandung, 2016)
The purpose of study is to exam the influence of the anchored instruction model on student’s problem solving ability of physics. The method used in this research is quasi-experiment and used non-equivalent control group design. Two samples consist of treatment class learned by using anchored instruction model and control class learned by using conventional model who were selected using purposive sampling techniques. The study was conducted in Abdi Karya senior high school Tanjungsari class X. The magnitude of the increase problem solving ability of students can be seen from the average N-Gain experiment class learners of 0.70 categorized being high and the average N-Gain control class learners of 0.59 categorized being middle. The effect of learning was analyzed by Mann Whitney U-test. The result showed that student’s problem solving ability of Physics on treatment class is better than the control class.